Fuelwood consumption in Central and Southern Chile: determinants and regional differences - Ferrada, Luz María; Torres, Gustavo; Montaña, Virginia; Sáez, Nicolás (Instituto de Ecología, A.C., 2022)
Firewood has been the most widely used wood energy source at the residential level in central and southern regions of Chile, and its high consumption in urban areas has seriously affected atmospheric quality. The objective was to analyze how economic, sociodemographic, and housing characteristics factors affect the firewood consumption of households living in six regions of central-southern Chile. First, the effect on the probability of consuming firewood was studied using logit estimates, and then on the amount consumed with Tobit models, both for the study area and by region. At a global level, it was observed that increases in household income increased the probability of consuming firewood and the quantities consumed, nevertheless, the impact among regions is different. In addition, firewood consumption decreases when faced with an increase in its price and increases when faced with an increase in the price of gas as a substitute good; sociodemographic aspects and housing characteristics, such as number of people in the household, age of the head of household and more square meters built, were positively related to firewood consumption. The results contribute to the formulation of regional public policies to address the problem